2010
DOI: 10.1002/cbic.201000182
|View full text |Cite
|
Sign up to set email alerts
|

Single‐ and Double‐Headed Chemical Probes for Detection of Active Cathepsin D in a Cancer Cell Proteome

Abstract: Activity-based proteomics employing active-site-directed chemical probes for enzymatic activity profiling in complex proteomes has greatly accelerated the functional annotation of proteins. [1,2] In protease research, new generations of activitybased probes have led to tremendous progress in our understanding of the biochemistry and physiology of cysteine peptidases over the last decade. [3,4] These probes were designed for in vitro applications as well as for in vivo monitoring in living cells and whole anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In this work, we developed clickable probes based on pepstatin to profile aspartic proteases by PAL. Although some studies have reported solid phase synthesis of aspartic protease probes, these made use of custom-synthesized building blocks or placed bulky cross-linkers at a distal position from the inhibitory scaffold that binds the active site cleft . We here showed that a minimal diazirine linker is suitable for incorporation into the peptide sequence of the general aspartic protease inhibitor pepstatin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we developed clickable probes based on pepstatin to profile aspartic proteases by PAL. Although some studies have reported solid phase synthesis of aspartic protease probes, these made use of custom-synthesized building blocks or placed bulky cross-linkers at a distal position from the inhibitory scaffold that binds the active site cleft . We here showed that a minimal diazirine linker is suitable for incorporation into the peptide sequence of the general aspartic protease inhibitor pepstatin.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have reported solid phase synthesis of aspartic protease probes, these made use of custom-synthesized building blocks 19 or placed bulky cross-linkers at a distal position from the inhibitory scaffold that binds the active site cleft. 18 We here showed that a minimal diazirine linker is suitable for incorporation into the peptide sequence of the general aspartic protease inhibitor pepstatin. Conveniently, the probes can be synthesized entirely on solid support by using commercially available building blocks.…”
Section: ■ Conclusionmentioning
confidence: 91%
See 1 more Smart Citation
“…1 H NMR (400 MHz, DMSO-d 6 ): 0.84 (3H, d, J = 6.8), 0.85 (3H, d, J = 6.8), 1.06−1.73 (31H, m), 1.97−2.05 (1H, m), 2.15 (1H, dd, J = 14.2, 6.3), 2.19 (2H, dd, J = 6.3, 6.1), 2.28 (1H, dd, J = 14.2, 7.8), 2.71−2.79 (1H, m), 3.28−3.37 (1H, m), 3.74−3.81 (1H, m), 3.93 (1H, dd, J = 8.0, 5.9), 3.82−3.87 (1H, m), 4.80 (1H, d, J = 5.5), 7.45 (1H, d, J = 9.2), 8.02 (1H, dd, J = 7.1, 4.4). 13 (3S,7S,8S)-7-Hydroxy-8-(4-hydroxybenzyl)-3-isopropyl-1,4,9-triazacyclohenicosane-2,5,10-trione (20). 1 H NMR (400 MHz, DMSOd 6 ): 0.84 (6H, d, J = 6.9), 1.02−1.46 (18H, m), 1.94−2.03 (1H, m), 2.03−2.10 (1H, m), 2.10−2.17 (1H, m), 2.21 (1H, dd, J = 14.1, 6.8), 2.26 (1H, dd, J = 14.1, 6.9), 2.57 (1H, dd, J = 13.9, 10.2), 2.69−2.77 (2H, m), 3.26−3.34 (1H, m), 3.81 (1H, dddd, J = 9.7, 9.5, 4.7, 1.6), 3.92−3.98 (3H, m), 6.59−6.63 (2H, m), 6.95−7.00 (2H, m), 7.58 (1H, br s), 7.60 (1H, d, J = 1.8), 7.96 (1H, dd, J = 7.0, 4.4), 9.05 (1H, br s).…”
Section: ■ Discussion and Conclusionmentioning
confidence: 99%
“…This linear pseudo-pentapeptide originally isolated from actinobacteria is effective against many aspartic proteases from the pepsin family with inhibition constants as low as 10 –10 M. Its potency is attributable to the nonproteinogenic amino acid statine [(3 S ,4 S )-4-amino-3-hydroxy-6-methylheptanoic acid], the hydroxyl group of which interacts with catalytic aspartate residues and acts as a transition-state analogue. Pepstatin A is widely used as a research tool for enzyme affinity purification, active site titration, imaging, and structural mapping of binding sites. However, its use as a therapeutic is limited due to its large size and unfavorable physicochemical properties including poor solubility, which are reflected in its low bioavailability and rapid clearance …”
Section: Introductionmentioning
confidence: 99%